Effect of body posture on visual acuity, refractive errorand binocular vision - Chen , Ai-Hong; Napisah Sai (Universiti Kebangsaan Malaysia, 2000)
The purpose of this study is to investigate the effect of the body postures on the visual acuity, refractive error and binocular vision. The near task body postures of thirty optometry students without pre-knowledge about the nature of the study were photographed from front view, side view and top view. The angles of the head tilt, body tilt and head rotation of the near task body posture for each subject were estimated based on the photographs. The habitual working distance and Harmon distance of each subject were also measured. The visual acuity, refractive error, amplitude of accommodation, positive and negatif relative accommodation, accommodation facility, accommodation lag, near point of convergence and heterophoria were tested for all subjects. Our results show that there was no significant effect of body posture on visual acuity, refractive error and binocular vision. Moderate head tilts, body tilts, head rotations and non-extreme habitual working distances of young adults do not seem to cause significant changes to their visual systems.